Latinx ESL Students' Successful English Language Transition at Community Colleges (Comparative & International Education Series, 2021)
Chapter 7|14 pages Latinx ESL Students' Successful English Language Transition at Community CollegesBy DuEwa M. FrazierThis phenomenological qualitative chapter illuminates the successful English language transition of Latinx English as a second language (ESL) students who matriculate to college English at three community colleges in the Northeastern and Mid-Atlantic regions of the United States. Data collection consisted of interviews with ten Latinx ESL students. This chapter focuses specifically on five Latinx ESL students who completed ESL courses, and English Composition I and English Composition II by the time of our one on one interviews. Three themes emerged as influencing factors on their matriculation to college English: student engagement in active learning, students' motivation to learn English, and faculty communication that guides English language learning. Students reported on their motivation to learn English. Students also discussed the faculty communication and instructional strategies that helped them persist to complete English coursework. This study has implications for teaching, curriculum, and student services.